The Influence of Knowledge and Work Attitude on Work Motivation and its Impact on The Performance of Nurses at RSUD Dr. Adjidarmo Rangkasbitung, Lebak District - Khaerunnissa, Intan; Setiawan, Heru (Pascasarjana Universitas Pasundan, 2023)
This study aims to determine and analyze the effect of knowledge and work attitudes on work motivation and their impact on the performance of nurses at RSUD Dr. Adjidarmo Rangkasbitung, Lebak Regency. The results of this study are expected to provide input for hospital leaders and nursing managers to use the results of this study to be taken into account in determining and providing appropriate interventions to improve the performance of nurses in providing nursing care services, especially in hospitals. The research method used is descriptive analysis and verification. The data collection used were interviews, questionnaires, and literature studies. The sample was taken using proportionate random sampling. Data collection in the field will be carried out in 2022. The data analysis technique uses Path Analysis. The results showed that in general the knowledge, work attitude, work motivation, and nurse performance tended to be less good. There is an influence of knowledge and work attitude on work motivation either partially or simultaneously and work motivation affects the performance of nurses in RSUD Dr. Adjidarmo Rangkasbitung, Lebak Regency.